Enhancing Engineering students’ Self-directed learning of Communication Skills: Is it Teacher Support and/or Peer support? - Joyce Debrah-Amofah; Abigail Konadu Aboagye; Gifty Serwah Mensah (Faculty of Education and Teacher Training of UIN Palopo, 2024)
Research shows that perceived teacher and peer support are essential to self-directed learning. Previous research has also examined the function of self-directed learning of Communication skills among Engineering undergraduates. Yet, there is a paucity of research into the influence of perceived teacher support and peer support in facilitating self-directed learning for the effective development of Communication skills. Thus, this study evaluated the effects of perceived teacher support and peer support on self-directed learning of Communication skills among Engineering students at technical universities in Ghana. This is a quantitative study with a cross-sectional survey design. A simple random sampling technique was employed to choose six technical universities, while a stratified random sampling technique was used to draw the sample sizes from each institution. Data were gathered from 1,189 first-year Engineering students. Multiple regression was used in analysing the data. The results revealed positive effects of teacher support and peer support on self-directed learning. Notwithstanding, the effect of teacher support was much stronger, indicating that teacher support best determines self-directed learning. Thus, it is imperative for teachers to discern the specific teacher activities that elicit favourable perceptions from students, in order to actively improve and refine these activities.